2018
DOI: 10.1016/j.envint.2018.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variability of personal environmental exposure to radio frequency electromagnetic fields in children in Europe

Abstract: The largest contributors to total personal environmental RF-EMF exposure were downlink and broadcast, and these exposures showed high repeatability. Urbanicity was the most important determinant of total exposure and mobile phone use was the most important determinant of uplink exposure. It is important to continue evaluating RF-EMF exposure in children as device use habits, exposure levels, and main contributing sources may change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
58
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 41 publications
7
58
0
1
Order By: Relevance
“…Published literature includes, among others, in‐situ indoor and outdoor measurements in schools and/or playgrounds with or without personal dosimeters for the evaluation of radiofrequency (RF) electromagnetic fields (EMF) and/or extremely low‐frequency (ELF) electric and magnetic fields [Juhász et al, ; Vermeeren et al, ; Verloock et al, , ; Liorni et al, ; Struchen et al, ; Gallastegi et al, ; Birks et al, ]. In Greece, a specific legislative framework for children's playgrounds was established in 2009 in order to ensure compliance with the established exposure limits to RF EMF and extremely low‐frequency (ELF) fields [International Commission on Non Ionizing Radiation Protection (ICNIRP), ].…”
mentioning
confidence: 99%
“…Published literature includes, among others, in‐situ indoor and outdoor measurements in schools and/or playgrounds with or without personal dosimeters for the evaluation of radiofrequency (RF) electromagnetic fields (EMF) and/or extremely low‐frequency (ELF) electric and magnetic fields [Juhász et al, ; Vermeeren et al, ; Verloock et al, , ; Liorni et al, ; Struchen et al, ; Gallastegi et al, ; Birks et al, ]. In Greece, a specific legislative framework for children's playgrounds was established in 2009 in order to ensure compliance with the established exposure limits to RF EMF and extremely low‐frequency (ELF) fields [International Commission on Non Ionizing Radiation Protection (ICNIRP), ].…”
mentioning
confidence: 99%
“…A recent study of Birks et al (21) reported results from personal RF EM environmental exposure levels in European children (Denmark, Netherland, Slovenia, Switzerland, and Spain) in the frequency range of 87.5 MHz -6 GHz. They found that the highest median exposure was outside (157.0 µW/m 2 ; approximately 0.5 V/m) and much lower at home (33.0 µW/m 2 ) or in school (35.1 µW/m 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…We report electric field strength values (in mV/m) in the results section, since that is most commonly reported in the literature [ 2 , 7 , 17 , 18 ]. We also compared the exposures with the International Commission on Non-Ionizing Radiation Protection (ICNIRP) reference levels for common frequency bands [ 19 ].…”
Section: Methodsmentioning
confidence: 99%